A Vernacular Historiography of the Punjabi Poetic Genre of the Kāfī: A Review of Shah Hussain, Bulleh Shah and Piro Preman’s Works - Latif , Ayesha; Akhtar, Rizwan (Journal of Research in Humanities, 2024)
This paper critically examines the formation of the Punjabi poetic tradition known as the kafi in the works of Shah Hussain, Bulleh Shah and Piro Preman, and presents an analysis of the genre as a vernacular medium. By situating the poems in the pre-modern Indian historical context, the article is an attempt to analyze the origin and the evolution of the poetic form known as the kafi. Drawing from scholars who propose a diverse and multifaceted outlook on the formation of Punjabi literary traditions, I review the genre from a framework known as a critical aesthetics of assimilation. In addition, this paper points out the structural and thematic changes introduced by the nineteenth-century poetess Piro Preman in the work called Āik Sau Sath Kāfīaṅ. I argue that the evolution of the kafi from Shah Hussain to Piro Preman’s compositions attests to the resilience and dynamism of the Punjabi poetic form.